The Value of the Correlation Coefficient Between the ICP Wave Amplitude and the Mean ICP Level (RAP) Combined With the Resistance to CSF Outflow (Rout) for Early Prediction of the Outcome Before Shunting in Posttraumatic Hydrocephalus - Zhang, Chao; Long, Si-Yu; You, Wen-dong; Xu, Xu-xu; Gao, Guo-Yi; Yang, Xiao-Feng (Frontiers in Neurology, 2022)
Objective To evaluate the value of the correlation coefficient between the ICP wave amplitude and the mean ICP level (RAP) and the resistance to CSF outflow (Rout) in predicting the outcome of patients with post-traumatic hydrocephalus (PTH) selected for shunting. Materials and Methods As a training set, a total of 191 patients with PTH treated with VP shunting were retrospectively analyzed to evaluate the potential predictive value of Rout, collected from pre-therapeutic CSF infusion test, for a desirable recovery level (dRL), standing for the modified rankin scale (mRS) of 0–2. Eventually, there were 70 patients with PTH prospectively included as a validation set to evaluate the value of Rout-combined RAP as a predictor of dRL. We calculated Rout from a CSF infusion test and collected RAP during continuous external lumbar drainage (ELD). Maximum RAP (RAPmax) and its changes relative to the baseline (ΔRAPmax%) served as specific parameters of evaluation. Results In the training set, Rout was proved to be a significant predictor of dRL to shunting, with the area under the curve (AUC) of 0.686 (p < 0.001) in receiver-operating characteristic (ROC) analysis. In the validation set, Rout alone did not present a significant value in the prediction of desirable recovery level (dRL). ΔRAPmax% after 1st or 2nd day of ELD both showed significance in predicting of dRL to shunting with the AUC of 0.773 (p < 0.001) and 0.786 (p < 0.001), respectively. Significantly, Rout increased the value of ΔRAPmax% in the prediction of dRL with the AUC of 0.879 (p < 0.001), combining with ΔRAPmax% after the 1st and 2nd days of ELD. RAPmax after the 1st and 2nd days of ELD showed a remarkable predictive value for non-dRL (Levels 3-6 in Modified Rankin Scale) with the AUC of 0.891 (p < 0.001) and 0.746 (p < 0.001). Conclusion Both RAP and Rout can predict desirable recovery level (dRL) to shunting in patients with PTH in the early phases of treatment. A RAP-combined Rout is a better dRL predictor for a good outcome to shunting. These findings help the neurosurgeon predict the probability of dRL and facilitate the optimization of the individual treatment plan in the event of ineffective or unessential shunting.